Feminisms of discontent : global contestations - Barnes, Ashleigh (Oxford university press, 2015)
Contributed articles presented at the Conference Feminisms of Discontent: Global Contestations: Debates on Gender and the Law, organized by the Centre for Women, Law and Social Change, O.P. Jindal Global University, in collaboration with Australian National University, held during February 18-20, 2011, at New Delhi.